Pengaruh Angka Melek Huruf Dan Angka Partisipasi Sekolah Terhadap Jumlah Kemiskinan Di Provinsi Sumatera Utara Tahun 2017-2023 - Ritonga, Jesika Ramadani; Ginting, Sansugiri; Naibaho, Erinna; Situmorang, Aelfi; Simarmata, Agung Pratama; Chairunisah, Chairunisah (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2024)
This study aims to analyze the impact of Literacy Rates (AMH) and School Enrollment Rates (APS) on poverty levels in North Sumatra Province from 2017 to 2023. Employing a quantitative causality approach, this research utilizes secondary data published by the Central Statistics Agency (BPS) of North Sumatra. Multiple linear regression analysis was applied to test the influence of independent variables on the dependent variable. The results show that (1) Literacy Rates do not significantly affect poverty levels, (2) School Enrollment Rates also do not significantly affect poverty levels, and (3) jointly, Literacy Rates and School Enrollment Rates account for 79.60% of the variance in poverty levels, with the remainder influenced by other factors not included in this study. The study recommends enhancing community-based education programs and increasing educational access to reduce poverty more effectively.